T-induced displacive phase transition of end-member Pb-lawsonite. (2nd January 2018) - Ende, Martin; Wunder, Bernd; Koch-Müller, Monika; Pippinger, Thoma.; Buth, Gernot; Giester, Gerald; Lengauer, Christian L.; Libowitzky, Eugen
Abstract: Pb-lawsonite, PbAl2 [(OH)2 |Si2 O7 ]·H2 O, space group Pbnm, was synthesized as crystals up to 15 μm × 5 μm × 5 μm in size by a piston cylinder technique at a pressure of ∼4 GPa and a temperature of 873 ± 10 K. Temperature-dependent powder and single-crystal X-ray diffraction (XRD) analyses partly using synchrotron radiation as well as Raman spectroscopic investigations reveal a phase transition around 445 K resulting in the Cmcm high-temperature structure. The transformation temperature is considerably higher than that of lawsonite around 273 K, which is characterized predominantly by proton order/disorder. The transition is confirmed using principal component analysis and subsequent hierarchical cluster analysis on both the powder XRD patterns and the Raman spectra. Furthermore, a non-uniform change is observed around 355 K, which is not as pronounced as the 445 K transition and apparently comes from enhanced hydrogen bonding, which stops the atom shifts in Pb-lawsonite. These are the same bonds that mainly characterize the phase transition in lawsonite around 273 K. In contrast, the structural transition of Pblawsonite at 445 K seems to originate from the interaction of the SiO4 tetrahedra and AlO6 octahedra framework with the Pb 2+ cation. The structural environment of Pb 2+ can be described by a 12-fold coordination above 445 K, which changes towards irregular ten-fold coordination below this temperature. An assignment of the O–H stretching Raman bands confirms moderately strong H bonds in Pb-lawsonite, whereas both strong and weak H bonds exist in lawsonite. Therefore, a further phase transition of Pblawsonite, similar to that of lawsonite around 273 K, is not expected.